Contributions from Multiple Nationalities for the Entrepreneurship Education - Lima, Edmilson de Oliveira; Cunha, Júlio Araújo Carneiro da; Nassif, Vânia Maria Jorge (REGEPE Entrepreneurship and Small Business Journal, 2020)
The purpose of this editorial is to introduce the special edition of the Iberoamerican Journal of Entrepreneurship and Small Business (REGEPE) on entrepreneurship education (EE). To this end, this editorial contains a brief contextualization, makes considerations on the theme, summarizes the main reasons for rejection of articles not included in the edition, and highlights contributions of the published articles, in order to boost the improvement of research on the theme in Brazil. The call for the edition challenged researchers to present different visions, theories, and practices of EE using the study of critical issues, such as needs for knowledge and differentiation from traditional education.